PENGARUH INOVASI TEKNOLOGI, LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN DENGAN INKLUSI KEUANGAN SEBAGAI VARIABEL INTERVENING KASUS UMKM DI JABODETABEK - Fitriana Nur Aini; Christina Dwi Astuti (STMIK Widuri Jakarta, 2023)
Purpose this study aims to examine the effect of technological innovation, financial literacy on financial performance with financial inclusion as an intervening variable. This type of research is quantitative research. The data used in this study is primary data. The population in this study is all MSME actors and the sample of this study is food and beverage MSMEs in Jabodetabek. The sampling technique uses the hair formula by multiplying 29 indicators by five. From this data, 145 respondents were obtained. The analysis used is a multip1e 1inear regression ana1ysis method. The resu1ts of the ana1ysis show that technological innovation and financia11iteracy have a positive effect on the financial inclusion of food and beverage MSMEs in Jabodetabek and vice versa technological innovation does not directly affect the financial performance of food and beverage MSMEs in Jabodetabek, but is mediated by financial inclusion. Financial literacy has a direct effect on the financia1 performance of food and beverage MSMEs in Jabodetabek and is not mediated by financial inclusion.